Risk Management of OHS for Landfilling Construction in Talangagung Edu-Tourism Landfill - Dhymas Sulistyono Putro; Arief Rachmansyah; Bagyo Yanuwiadi (Journal of Indonesian Tourism and Development Studies, 2019)
Talangagung Edu-Tourism Landfill is one of the landfills in Indonesia that leads to the Edu-Tourism Landfill. Thus, there is a need for OHS risk management for workers to improve service to tourists. Aim of the study is to determine, identify, analyze, and compile hazard sources or injury potential and risk assessment in activities from technical workers in the work area of Talangagung Edu-Tourism, as well as risk control that can be applied to reduce the consequences of each hazard sources or injury potential. The data collected through observations, interviews, and brainstorming to all technical workers and a chief. The processing of occupational health and safety risk management data was based on the Job Safety Analysis (JSA) concept. The hazard source or injury potential identification finds 7 activities. Each of which several steps along with their hazard source or injury potential and consequences identified. There are 43 hazard sources or injury potentials, from which, based on the risk assessment, 14 are extreme (E), 12 are high (H), 2 are medium (M), and 15 are low (L). The control divided into two. Eight of the controls conducted by the management of Talangagung Edu-Tourism and seventeen of the rest controls suggested by the researcher. By applying OHS Risk Management, they will increase the number of tourists because it improves the quality of the workers in service.Keywords: Job Safety analysis, OHS, risk management.